Method for assisting electrolysis of solid oxide electrolytic tank by ammonia gas, symmetrical electrode and preparation method of symmetrical electrode

By introducing ammonia-assisted technology and high-entropy alloy coating catalysts into SOECs, the problems of the rate limit of anodic oxygen precipitation reaction and insufficient activation capacity of perovskite oxides in traditional SOECs are solved, and CO2 electrolytic efficiency and electrode material stability are improved , achieving low energy consumption and high efficiency electrolysis.

CN119194467APending Publication Date: 2024-12-27中国地质大学深圳研究院 +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411333462.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The kinetic speed limit of the oxygen precipitation reaction of the anode in traditional SOECs leads to high oxygen partial pressure hindering the transfer of oxygen ions, requiring a large amount of external energy, and the activation and oxidation capacity of the perovskite oxide electrode is limited, making it difficult to improve the CO2 electrolytic efficiency.

Method used

Using ammonia-assisted solid oxide electrolytic cell method, NH3 is introduced into the anode side for oxidation, and green and non-polluting N2 and H2O are generated, instead of oxygen precipitation reaction, reduce the anode oxygen partial pressure, and perform CO2 electrolysis on the cathode side, using high The doped cerium oxide catalyst coated with entropy alloy increases the reaction rate and efficiency, and combines the utilization of waste heat resources to reduce energy consumption.

Benefits of technology

Improve the reaction efficiency of SOEC anode, reduce the power demand for CO2 electrical reduction, reduce energy consumption, extend the service life of electrode materials, and solve the carbon deposit problem of traditional nanometal catalysts through high-entropy alloy catalysts, achieving structural stability and efficient catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194467A_ABST
    Figure CN119194467A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolysis, in particular to a method for assisting electrolysis of a solid oxide electrolytic tank by ammonia gas, a symmetric electrode and a preparation method of the symmetric electrode. According to the method for assisting electrolysis of the solid oxide electrolytic tank with the ammonia gas, NH3 is introduced into the anode side of the solid oxide electrolytic tank for oxidation, CO2 and / or H2O is introduced into the cathode side of the solid oxide electrolytic tank, and the CO2 and / or H2O are / is electrolyzed. The symmetric electrode disclosed by the invention is applied to the solid oxide electrolytic tank, and a symmetric electrode catalyst is square fluorite type cerium oxide and high-entropy alloy which is separated out from doped cerium oxide in situ. The conventional dynamic slow oxygen evolution reaction on the SOEC anode is replaced by a favorable NH3 oxidation reaction, so that the oxygen partial pressure on the anode side can be reduced, the CO2 reduction reaction rate of the cathode is improved, and meanwhile, the power demand of CO2 electroreduction is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrolysis technology, and in particular to an ammonia-assisted solid oxide electrolysis cell electrolysis method and a symmetrical electrode and a preparation method thereof. Background Art

[0002] In conventional SOECs, the oxygen evolution reaction (OER) at the anode of the SOEC involves a four-electron transfer process, which is related to the CO 2 Compared with the two-electron transfer process of reduction, this is a kinetically rate-limiting step. In addition, the high anodic oxygen partial pressure hinders the transfer of oxygen ions from the cathode to the anode. This requires a large amount of external energy to drive the electrolysis reaction. Therefore, replacing the slow OER with a more thermodynamically and kinetically favorable reaction can improve CO 2 Electrolytic performance. Summary of the invention

[0003] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a method for electrolysis in an ammonia-assisted solid oxide electrolytic cell and a symmetrical electrode and a method for preparing the same.

[0004] The present invention provides a method for electrolysis in a solid oxide electrolytic cell assisted by ammonia, wherein NH 3 Oxidation is carried out by introducing CO on the cathode side 2 and\orH 2 O, CO 2 and\orH 2 O is electrolyzed.

[0005] The symmetrical electrode of the present invention is applied to the solid oxide electrolytic cell, and the catalyst of the symmetrical electrode is fluorite-type cerium oxide and a high entropy alloy in situ precipitated from doped cerium oxide.

[0006] Furthermore, the chemical formula of doped cerium oxide is Ce 0.9 (M) 0.1 O 2-δ The high entropy alloy is M nanoparticles, and M is an equimolar combination of any five transition metal elements Fe, Ni, Ru, Cu, Co, Cr, Pt, Ir and Rh.

[0007] Furthermore, the high entropy M alloy is generated by in-situ exsolution of metal-doped cerium oxide.

[0008] Furthermore, the size of high entropy M alloy is between 50 and 150 nm.

[0009] A method for preparing the symmetrical electrode as described above comprises the following steps: S1: Preparation of cubic fluorite-doped cerium oxide Ce by sol-gel method 0.9 (M)0.1 O 2-δ Precursor; S2: The precursor and the binder are mixed and ground to prepare a slurry, which is coated on the surface of the solid electrolyte and sintered to prepare a battery; S3: The battery is in-situ reduced at a certain operating temperature and in a reducing atmosphere, and the electrode precursor is in-situ formed into doped cerium oxide coated with high entropy alloy M particles, so as to obtain the symmetrical electrode.

[0010] Further, in step S1, cubic fluorite-doped cerium oxide Ce is prepared 0.9 (M) 0.1 O 2-δ The specific operations of the precursor are: S11: Dissolve a certain amount of citric acid in water, and then dissolve Ce source and M source in a stoichiometric ratio, where M is any five of Fe, Ni, Ru, Cu, Co, Cr, Pt, Ir and Rh. After all the above metal salts are dissolved, add concentrated nitric acid and EDTA, and then adjust the pH to 7-8 with ammonia water, heat and stir until clear, and then heat to obtain a gel; S12: The powder obtained by heat preservation and carbon removal of the gel obtained in step S11 is sintered at high temperature to obtain cubic fluorite cerium oxide Ce. 0.9 (M) 0.1 O 2-δ Precursor powder.

[0011] Furthermore, in step S11, the molar ratio of citric acid: metal ion: EDTA is 1:1:1.5; in step S12, the gel is kept at 600 °C for 4 hours for decarbonization, and then the obtained powder is placed in a muffle furnace and sintered at 800 °C for 5 hours.

[0012] Furthermore, in step S2, the binder is pinene alcohol containing 7.5-10 wt.% ethyl cellulose; and the mass ratio of the precursor to the binder is 1:1.5.

[0013] Furthermore, in step S3, the operating temperature is 800-900 °C, the reducing atmosphere is pure hydrogen, and the in-situ reduction time is 30-90 min.

[0014] The significant advantages of the present invention are: 1. In order to improve the efficiency of the anode reaction and reduce the cost, the present invention proposes anode NH 3 The auxiliary method is to conduct NH 3 Oxidation to generate green and pollution-free N 2 and H 2 O, while releasing electrons, which can participate in the oxidation reaction of the fuel, improving the reaction rate and efficiency. 2Electrolysis, NH 3 Oxidation can also work synergistically with cathode fuel reduction to promote the cathode CO2 reduction reaction kinetics. The traditional kinetically slow oxygen evolution reaction at the SOEC anode is replaced by a favorable NH 3 The oxidation reaction can reduce the oxygen partial pressure on the anode side and increase the CO 2 Reduction reaction rate, while greatly reducing CO 2 Power requirements for electroreduction. NH 3 It has the advantages of low price, non-flammable, easy to transport and store, and complete industrial infrastructure. 3 Oxidation is well matched to SOEC in terms of operating temperature (600~900 °C). 3 The high heat demand of auxiliary SOEC can be obtained by utilizing waste heat resources. The heat can come from industrial waste heat, concentrated solar panels or waste heat electricity, etc. Therefore, the present invention provides a new idea and method for SOEC to stabilize electrolysis and reduce energy consumption, and provides a new application for the recycling of industrial waste ammonia and industrial waste heat.

[0015] 2. The present invention utilizes a sol-gel method and an in-situ dissolution method to prepare for the first time an electrode having a doped cerium oxide catalyst coated with high entropy alloy M particles. The doped cerium oxide catalyst coated with high entropy alloy M particles is a structurally ordered heterogeneous structure material. The high entropy alloy @ doped cerium oxide electrode is prepared by the in-situ dissolution method. In the battery operating temperature range (800-900 °C), the electrode is in-situ reduced to precipitate a high entropy alloy on the surface. The high entropy alloy is tightly combined with the doped cerium oxide matrix, has good dispersibility and good stability, and can effectively solve the problems of carbon deposition and agglomeration that are easy to occur in traditional nano-metal catalysts during the deposition process.

[0016] 3. Traditional SOEC electrode materials, perovskite oxides, usually exhibit limited NH 3 The high entropy alloy M particles prepared by the present invention coated with doped cerium oxide catalyst have an adjustable electronic structure and excellent structural stability between high entropy metals, which can not only improve the electronic conductivity of the electrode, but also improve CO 2 With NH 3 The adsorption and catalytic activity are suitable as symmetrical electrode materials for SOEC.

[0017] 4. The electrode preparation method of the present invention is synthesized under simple conditions, the method is simple, easy to implement, low-cost and has good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1a The conventional CO 2 Thermodynamic analysis diagram of electrolysis; Figure 1b NH of Example 1 3 Assisting SOEC to CO 2 Thermodynamic analysis diagram of electrolysis; Figure 2a Ce prepared by sol-gel method in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ CuFeNiRuCo@Ce prepared by precursor and in-situ reduction method 0.9 (CuFeNiRuCo) 0.1 O 2-δ (abbreviated as HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ XRD pattern of Figure 2b HE@Ce prepared by in-situ reduction method 0.9 (CuFeNiRuCo) 0.1 O 2-δ XRD refinement pattern of Figure 3a The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ SEM image of the precursor; Figure 3b HE@Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ SEM images of Figure 4a The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Cu 2p XPS comparison chart; Figure 4b The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Fe 2p XPS comparison chart; Figure 4c The Ce prepared in Example 10.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Ni 2p XPS comparison chart; Figure 4d The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Ru 3p XPS comparison chart; Figure 4e The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Co 2p XPS comparison chart; Figure 4f The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Ce 3d XPS comparison chart; Figure 4g The Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ O 1s XPS comparison chart; Figure 5 HE@Ce prepared in Example 1 0.9 (CuFeNiRuCo) 0.1 O 2-δ Thermodynamic calculation diagram of the reduction of each metal oxide; Figure 6a The conventional CO 2 Electrolysis and NH3 Auxiliary CO 2 Current-voltage diagram for electrolysis; Figure 6b The conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2 Impedance plot at open circuit voltage for electrolysis; Figure 7 The conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2 Comparison chart of power consumption during electrolysis; Figure 8 For NH 3 Assisting SOEC to CO 2 Schematic diagram of the electrolysis structure. DETAILED DESCRIPTION

[0019] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0020] Embodiment 1: According to the chemical formula Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ , weigh Ce(NO 3 ) 3 6H 2 O, Cu(NO 3 ) 2 9H 2 O, Fe(NO 3 ) 2 9H 2 O.Ni(NO 3 ) 2 6H 2 O.C 8 H 12 O 9 Ru 2 、Co(NO 3 ) 2 6H 2O was dissolved in 100 mL of deionized water, citric acid was added in a ratio of 1:1 between metal ions and citric acid and stirred continuously until completely dissolved, then 20 mL of concentrated nitric acid was added, and EDTA powder was added in a ratio of 1:1.5 between metal ions and EDTA, and the pH value of the solution was adjusted to 7 with ammonia water. After stirring until clear, it was placed in a microwave oven to obtain a gel. The gel was kept at 600 °C for 4 h to fully decompose the organic matter therein. The obtained powder was then placed in a muffle furnace and sintered at 800 °C for 5 h to obtain Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursor.

[0021] Take the Ce prepared above 0.9 (CuFeNiRuCo) 0.1 O 2-δ The precursor is added with 7.5-10 wt.% ethyl cellulose and pinene alcohol, and the mass ratio of the precursor to pinene alcohol is 1:1.5. The mixture is mixed and ground for several hours to obtain the electrode slurry. The slurry is evenly coated on both sides of the dense LSGM electrolyte with a thickness of 240 μm by screen printing, and the electrode is dried. After drying, it is sintered in air atmosphere at 1050 °C for 4 h to complete the preparation of the single cell.

[0022] The single cell was packaged and tested. The cathode and anode were first charged with pure H at 800 °C. 2 (~3% H 2 O) for 1 h, the precursor powder was reduced to HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Then pass N 2 The excess H 2 After cleaning, the anode is fed with NH 3 , CO is introduced into the cathode 2 Conduct SOEC electrolysis test. In-situ reduction precipitation of high entropy alloy can be expressed by equation 1-1: (1-1) See Appendix 1. From the comparison of thermodynamic and operating parameters of different electrolyzers commonly used in industry, it can be seen that SOEC is more efficient than the commonly used low-temperature electrolyzer (~ 80°C). This is mainly because the low-temperature electrolyzer should be operated at a high voltage (>1.7 V), producing additional heat and conversion efficiency loss. When electrolyzing at high temperature (~800°C), compared with the traditional SOEC electrolysis of CO 2 , NH 3 The auxiliary SOEC has the lowest thermoneutral voltage and thus converts CO per unit volume. 2 or H 2O will consume less energy. In addition, NH 3 The auxiliary SOEC has a higher heat demand TΔS, indicating that more Joule heat can be utilized to obtain higher energy conversion efficiency. 3 In the auxiliary SOEC mode, the power demand ΔG is less, the heat demand TΔS is more, and the gas production rate is faster at the same operating voltage. 3 The high heat demand of the auxiliary SOEC can be obtained by utilizing waste heat resources. The heat can come from industrial waste heat, concentrated solar panels or waste heat power, etc. For example, the steel industry is a heat-intensive industry (accounting for 4-5% of the world's total energy consumption), more than half of which is wasted. 3 Assisting SOEC to enter the steel industry will significantly improve energy utilization efficiency.

[0023] Table 1

[0024] See attached Figure 1a , the SOEC assembled according to the first embodiment of the present invention is subjected to conventional CO 2 Thermodynamic analysis diagram of electrolysis. See attached Figure 1b , is NH assembled according to the first embodiment of the present invention 3 Assisting SOEC to CO 2 Thermodynamic analysis of electrolysis. The results show that the anode NH 3 Under oxidative conditions, the total reaction Gibbs free energy at 800 °C increases from 189.21 kJ mol -1 Reduced to -69.37 kJ mol -1 . It shows that the theoretical calculation of NH 3 The energy requirement of auxiliary SOEC is significantly lower than that of conventional SOEC. 3 The thermal effect of the oxidation reaction can provide the heat required for the operation of SOEC. At the same time, it can reduce the oxygen partial pressure at the anode, thereby accelerating the CO 2 Kinetics of reduction reactions.

[0025] See attached Figure 2a , is Ce prepared by sol-gel method according to the technical scheme of this embodiment 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursor and CuFeNiRuCo@Ce prepared by in-situ exsolution method 0.9 (CuFeNiRuCo) 0.1 O 2-δ (Abbreviated as: HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ). The results show that the precursor material is a cubic fluorite phase structure with a space group of Fm-3m. After in-situ reduction, the peak of the additional high entropy metal CuFeNiRuCo appears. The reduced material includes cubic fluorite-type doped cerium oxide and high entropy alloy CuFeNiRuCo precipitated in-situ on the surface of cerium oxide.

[0026] See attached Figure 2b HE@Ce prepared by in-situ dissolution method according to the technical scheme of this embodiment 0.9 (CuFeNiRuCo) 0.1 O 2-δ XRD refinement diagram. The results show that the precipitated high entropy alloy CuFeNiRuCo has a space group of Fm-3m and accounts for 3.43% of the mass ratio of the main phase of doped cerium oxide.

[0027] See attached Figure 3a , is Ce prepared according to the technical scheme of this embodiment 0.9 (CuFeNiRuCo) 0.1 O 2-δ SEM image of the precursor. The results show that the powder is loose and porous, which is conducive to the diffusion of gas phase species. Figure 3b , HE@Ce prepared according to the technical solution of this embodiment 0.9 (CuFeNiRuCo) 0.1 O 2-δ The results show that the high entropy alloy CuFeNiRuCo is precipitated from the main phase of ceria doped with cerium oxide, and the particle size is between 50 and 150 nm.

[0028] See attached Figure 4a -g, Ce prepared according to the technical scheme of this embodiment 0.9 (CuFeNiRuCo) 0.1 O 2-δ Precursors and HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Cu 2p , Fe 2p , Ni 2p , Ru 3p ,Co 2p , Ce 3d , O 1s XPS comparison chart; After reduction, there is Cu in the XPS spectra of Cu, Fe, Ni, Ru and Co. 0 , Fe 0 , Ni 0 , Ru 0 and Co 0 The signal indicates that some Cu, Fe, Ni, Ru and Co are reduced to single elements.3d The XPS comparison chart uses u and v to represent 3d 5 / 2 and 3d 3 / 2 Spin-orbit component. Ce 4+ The peaks include u''' = 915.92, u'' = 906.72, u = 900.12, v''' = 897.53, v'' = 888.27 and v = 881.60 eV, while Ce 3+ The peaks are observed at u' = 902.13 and v' = 883.54 eV, respectively. 0.9 (CuFeNiRuCo) 0.1 O 2-δ Ce in the precursor sample 4+ Dominant, HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ Center 3+ The peak of the sample is stronger than that of the oxidized sample. This is because after heat treatment in a reducing atmosphere, part of the Ce 4+ Reducing to Ce 3+ .O 1s XPS comparison chart shows that after reduction, HE@Ce 0.9 (CuFeNiRuCo) 0.1 O 2-δ The lattice oxygen content decreases, the surface oxygen vacancies increase, and the binding energy shifts negatively, which is conducive to the formation and diffusion of oxygen vacancies.

[0029] See attached Figure 5 , HE@Ce prepared according to the technology of this embodiment 0.9 (CuFeNiRuCo) 0.1 O 2-δ Thermodynamic calculation diagram of the reduction of each metal oxide in. The Gibbs free energy formula for the reduction of metal oxides to metals can be expressed by equations 1-2 to 1-7: (1-2) (1-3) (1-4) (1-5) (1-6) (1-7) The results show that at 800 °C, Cu, Fe, Ni, Ru and Co can all be reduced to elemental metals. The Gibbs free energy relationship is RuO2 (-252.219 kJ mol -1 ) <CuO(-129.084 kJ mol -1 ) <NiO(-46.972 kJ mol -1 ) <CoO(-30.752 kJ mol -1 ) <Fe 2 O 3 (-26.456 kJ mol -1 ) <CeO 2 (489.234 kJ mol -1 ). Among them, RuO 2 The Gibbs free energy is more negative, indicating that Ru is better at desolvating in the lattice than other metals. 2 Cannot be reduced to metal.

[0030] Figure 8 For NH 3 Assisting SOEC to CO 2 Schematic diagram of the electrolysis structure.

[0031] See attached Figure 6a , is the conventional CO of SOEC assembled according to the first embodiment of this invention 2 Electrolysis and NH 3 Assisting SOEC to CO 2 The current-voltage diagram of electrolysis. The results show that the anode NH 3 The assist significantly reduces the applied voltage. For example, for 1.3 A cm -2 At a current density of 1.48 V, the applied voltage of conventional SOEC is 1.48 V, while for NH 3 To assist SOEC, the applied voltage was reduced to 0.66 V. NH 3 The electrolysis current density of the assisted SOEC at 0.6 V is 0.86 A cm higher than that of the conventional SOEC -2 .

[0032] See attached Figure 6b , according to the SOEC of this embodiment 1, the conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2 Impedance diagram of electrolysis at open circuit voltage. NH 3 After that, the polarization resistance at 800 °C was significantly reduced to that of conventional CO 2 13% of electrolysis.

[0033] See attached Figure 7 , according to the SOEC of this embodiment 1, the conventional CO 2 Electrolysis and NH 3Auxiliary CO 2 Comparison of power consumption during electrolysis. At a current density of 1.3 A cm -2 and 800 °C, the power consumption per cubic meter of CO increases from the conventional 3.54 kWhm to -3 Down to NH 3 1.58 kWh m for auxiliary SOEC -3 The electricity consumption of CO was significantly reduced by 55.4%. In addition, NH 3 Assisting the oxidation reaction in SOEC not only reduces the energy consumption of the system, but also further improves the overall efficiency of the cell by reducing the oxygen partial pressure at the anode. This effect of reducing the oxygen partial pressure helps to reduce the oxidative stress on the electrolyte and electrode materials, thereby extending the service life of the SOEC, making NH 3 Auxiliary SOEC shows broader application prospects in the fields of energy conversion and chemical industry.

[0034] Embodiment 2: According to the chemical formula Ce 0.9 (CuFePtCrIr) 0.1 O 2-δ , weigh Ce(NO 3 ) 3 6H 2 O, Cu(NO 3 ) 2 9H 2 O, Fe(NO 3 ) 2 9H 2 O, H 14 C l6 O 6 Pt, C 6 H 9 O 6 Cr, C 14 H 27 Ir 3 O 18 Dissolve in 100 mL of deionized water in turn, add citric acid at a ratio of 1:1 between metal ions and citric acid and stir continuously until completely dissolved, then add 20 mL of concentrated nitric acid, and add EDTA powder at a ratio of 1:1.5 between metal ions and EDTA, and adjust the solution pH to 7 with ammonia water, stir until clear and heat in a microwave oven to obtain a gel. Take the gel and keep it at 600 °C for 4 h to fully decompose the organic matter in it. Then, place the obtained powder in a muffle furnace and sinter at 800 °C for 5 h to obtain Ce 0.9 (CuFePtCrIr) 0.1 O 2-δ Precursor.

[0035] Take the Ce prepared above 0.9 (CuFePtCrIr) 0.1 O 2-δ The precursor is added with 7.5-10 wt.% ethyl cellulose and pinene alcohol, and the mass ratio of the precursor to pinene alcohol is 1:1.5. The mixture is mixed and ground for several hours to obtain the electrode slurry. The slurry is evenly coated on both sides of the dense LSGM electrolyte with a thickness of 240 μm by screen printing, and the electrode is dried. After drying, it is sintered in air atmosphere at 1050 °C for 4 h to complete the preparation of the single cell.

[0036] The single cell was packaged and tested. The cathode and anode were first charged with pure H at 800 °C. 2 (~3% H 2 O) for 1 h, the precursor powder was reduced to CuFePtCrIr@Ce 0.9 (CuFePtCrIr) 0.1 O 2-δ Then pass N 2 The excess H 2 After cleaning, the anode is fed with NH 3 , CO is introduced into the cathode 2 Conduct SOEC electrolysis test. In-situ reduction precipitation of high entropy alloy can be expressed by equation 2-1: (2-1) In order to carry out conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2 The electrolysis performance results show that the applied voltage of the conventional SOEC is 1.48 V, while for NH 3 To assist SOEC, the applied voltage was reduced to 0.54 V. NH 3 The electrolysis current density of the assisted SOEC at 0.6 V is 0.97 A cm higher than that of the conventional SOEC. -2 The polarization resistance at 800 °C is significantly reduced to that of conventional CO 2 11% of electrolysis.

[0037] Embodiment three: According to the chemical formula Ce 0.9 (CrPtIrRuRh) 0.1 O 2-δ , weigh Ce(NO 3 ) 3 6H 2 O.C 6 H 9 O 6 Cr、H 14 C l6O 6 Pt, C 14 H 27 Ir 3 O 18 , C 8 H 12 O 9 Ru 2 , RhCl 3 Dissolve in 100 mL of deionized water in turn, add citric acid at a ratio of 1:1 between metal ions and citric acid and stir continuously until completely dissolved, then add 20 mL of concentrated nitric acid, and add EDTA powder at a ratio of 1:1.5 between metal ions and EDTA, and adjust the solution pH to 7 with ammonia water, stir until clear and heat in a microwave oven to obtain a gel. Take the gel and keep it at 600 °C for 4 h to fully decompose the organic matter in it. Then, place the obtained powder in a muffle furnace and sinter at 800 °C for 5 h to obtain Ce 0.9 (CrPtIrRuRh) 0.1 O 2-δ Precursor.

[0038] Take the Ce prepared above 0.9 (CrPtIrRuRh) 0.1 O 2-δ The precursor is added with 7.5-10 wt.% ethyl cellulose and pinene alcohol, and the mass ratio of the precursor to pinene alcohol is 1:1.5. The mixture is mixed and ground for several hours to obtain the electrode slurry. The slurry is evenly coated on both sides of the dense LSGM electrolyte with a thickness of 240 μm by screen printing, and the electrode is dried. After drying, it is sintered in air atmosphere at 1050 °C for 4 h to complete the preparation of the single cell.

[0039] The single cell was packaged and tested. The cathode and anode were first charged with pure H at 800 °C. 2 (~3% H 2 O) for 1 h, the precursor powder was reduced to CrPtIrRuRh@Ce 0.9 (CrPtIrRuRh) 0.1 O 2-δ Then pass N 2 The excess H 2 After cleaning, the anode is fed with NH 3 , CO is introduced into the cathode 2 Conduct SOEC electrolysis test. In-situ reduction precipitation of high entropy alloy can be expressed by equation 3-1: (3-1) In order to carry out conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2The electrolysis performance results show that the applied voltage of the conventional SOEC is 1.48 V, while for NH 3 To assist SOEC, the applied voltage was reduced to 0.59 V. NH 3 The electrolysis current density of the assisted SOEC at 0.6 V is 0.91 A cm higher than that of the conventional SOEC. -2 The polarization resistance at 800 °C is significantly reduced to that of conventional CO 2 12% of electrolysis.

[0040] Embodiment 4: According to the chemical formula Ce 0.9 (RhFeNiRuIr) 0.1 O 2-δ , weigh Ce(NO 3 ) 3 6H 2 O、RhCl 3 、Fe(NO 3 ) 2 9H 2 O.Ni(NO 3 ) 2 6H 2 O.C 8 H 12 O 9 Ru 2 , C 14 H 27 Ir 3 O 18 Dissolve in 100 mL of deionized water in turn, add citric acid at a ratio of 1:1 between metal ions and citric acid and stir continuously until completely dissolved, then add 20 mL of concentrated nitric acid, and add EDTA powder at a ratio of 1:1.5 between metal ions and EDTA, and adjust the solution pH to 7 with ammonia water, stir until clear and heat in a microwave oven to obtain a gel. Take the gel and keep it at 600 °C for 4 h to fully decompose the organic matter in it. Then, place the obtained powder in a muffle furnace and sinter at 800 °C for 5 h to obtain Ce 0.9 (RhFeNiRuIr) 0.1 O 2-δ Precursor.

[0041] Take the Ce prepared above 0.9 (RhFeNiRuIr) 0.1 O 2-δThe precursor is added with 7.5-10 wt.% ethyl cellulose and pinene alcohol, and the mass ratio of the precursor to pinene alcohol is 1:1.5. The mixture is mixed and ground for several hours to obtain the electrode slurry. The slurry is evenly coated on both sides of the dense LSGM electrolyte with a thickness of 240 μm by screen printing, and the electrode is dried. After drying, it is sintered in air atmosphere at 1050 °C for 4 h to complete the preparation of the single cell.

[0042] The single cell was packaged and tested. The cathode and anode were first charged with pure H at 800 °C. 2 (~3% H 2 O) for 1 h, the precursor powder was reduced to RhFeNiRuIr@Ce 0.9 (RhFeNiRuIr) 0.1 O 2-δ Then pass N 2 The excess H 2 After cleaning, the anode is fed with NH 3 , CO is introduced into the cathode 2 Conduct SOEC electrolysis test. In-situ reduction precipitation of high entropy alloy can be expressed by equation 4-1: (4-1) In order to carry out conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2 The electrolysis performance results show that the applied voltage of the conventional SOEC is 1.48 V, while for NH 3 To assist SOEC, the applied voltage was reduced to 0.61 V. NH 3 The electrolysis current density of the assisted SOEC at 0.6 V is 0.90 A cm higher than that of the conventional SOEC -2 The polarization resistance at 800 °C is significantly reduced to that of conventional CO 2 12% of electrolysis.

[0043] Embodiment five: According to the chemical formula Ce 0.9 (CrPtNiRhCo) 0.1 O 2-δ , weigh Ce(NO 3 ) 3 6H 2 O.C 6 H 9 O 6 Cr、H 14 C l6 O 6 Pt、Ni(NO 3 ) 2 6H2 O、RhCl 3 、Co(NO 3 ) 2 6H 2 O was dissolved in 100 mL of deionized water, citric acid was added in a ratio of 1:1 between metal ions and citric acid and stirred continuously until completely dissolved, then 20 mL of concentrated nitric acid was added, and EDTA powder was added in a ratio of 1:1.5 between metal ions and EDTA, and the pH value of the solution was adjusted to 7 with ammonia water. After stirring until clear, it was placed in a microwave oven to obtain a gel. The gel was kept at 600 °C for 4 h to fully decompose the organic matter therein. The obtained powder was then placed in a muffle furnace and sintered at 800 °C for 5 h to obtain Ce 0.9 (CrPtNiRhCo) 0.1 O 2-δ Precursor.

[0044] Take the Ce prepared above 0.9 (CrPtNiRhCo) 0.1 O 2-δ The precursor is added with 7.5-10 wt.% ethyl cellulose and pinene alcohol, and the mass ratio of the precursor to pinene alcohol is 1:1.5. The mixture is mixed and ground for several hours to obtain the electrode slurry. The slurry is evenly coated on both sides of the dense LSGM electrolyte with a thickness of 240 μm by screen printing, and the electrode is dried. After drying, it is sintered in air atmosphere at 1050 °C for 4 h to complete the preparation of the single cell.

[0045] The single cell was packaged and tested. The cathode and anode were first charged with pure H at 800 °C. 2 (~3% H 2 O) for 1 h, the precursor powder was reduced to CrPtNiRhCo@Ce 0.9 (CrPtNiRhCo) 0.1 O 2-δ Then pass N 2 The excess H 2 After cleaning, the anode is fed with NH 3 , CO is introduced into the cathode 2 Conduct SOEC electrolysis test. In-situ reduction precipitation of high entropy alloy can be expressed by equation 5-1: (5-1) In order to carry out conventional CO 2 Electrolysis and NH 3 Auxiliary CO 2 The electrolysis performance results show that the applied voltage of the conventional SOEC is 1.48 V, while for NH 3Assisted SOEC, the applied voltage was reduced to 0.67 V. NH 3 The electrolysis current density of the assisted SOEC at 0.6 V is 0.85 A cm higher than that of the conventional SOEC -2 The polarization resistance at 800 °C is significantly reduced to that of conventional CO 2 13% of electrolysis.

[0046] For matters not mentioned above, the prior art applies.

[0047] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for electrolysis in an ammonia-assisted solid oxide electrolysis cell, characterized in that: NH3 is introduced into the anode side of the solid oxide electrolysis cell, and CO2 and / or H2O is introduced into the cathode side to electrolyze CO2 and / or H2O.

2. A symmetrical electrode, characterized in that: Applied to the solid oxide electrolytic cell described in claim 1, the symmetrical electrode catalyst is fluorite-type cerium oxide and a high entropy alloy in situ precipitated from doped cerium oxide.

3. The symmetrical electrode according to claim 2, characterized in that: The chemical formula of doped cerium oxide is Ce 0.9 (M) 0.1 O 2-δ The high entropy alloy is M nanoparticles, and M is an equimolar combination of any five transition metal elements Fe, Ni, Ru, Cu, Co, Cr, Pt, Ir and Rh.

4. The symmetrical electrode according to claim 2, characterized in that: The high entropy M alloy is generated by in-situ exsolution of metal-doped cerium oxide.

5. The symmetrical electrode according to claim 2, characterized in that: The size of high entropy M alloys is between 50 and 150 nm.

6. A method for preparing a symmetrical electrode according to any one of claims 2 to 5, characterized in that: The steps include: S1: Preparation of cubic fluorite-doped cerium oxide Ce by sol-gel method 0.9 (M) 0.1 O 2-δ Precursor; S2: The precursor and the binder are mixed and ground to prepare a slurry, which is coated on the surface of the solid electrolyte and sintered to prepare a battery; S3: The battery is in-situ reduced at a certain operating temperature and in a reducing atmosphere, and the electrode precursor is in-situ formed into doped cerium oxide coated with high entropy alloy M particles, so as to obtain the symmetrical electrode.

7. The preparation method according to claim 6, characterized in that: In step S1, cubic fluorite-doped cerium oxide Ce is prepared 0.9 (M) 0.1 O 2-δ The specific operations of the precursor are: S11: dissolving a certain amount of citric acid in water, and then dissolving Ce source and M source in a stoichiometric ratio, where M is any five of Fe, Ni, Ru, Cu, Co, Cr, Pt, Ir and Rh; after all the above metal salts are dissolved, add concentrated nitric acid and EDTA, and then adjust the pH to 7-8 with ammonia water, heat and stir until clear, and then heat to obtain a gel; S12: The powder obtained by heat preservation and carbon removal of the gel obtained in step S11 is sintered at high temperature to obtain cubic fluorite cerium oxide Ce. 0.9 (M) 0.1 O 2-δ Precursor powder.

8. The preparation method according to claim 7, characterized in that: In step S11, the molar ratio of citric acid: metal ion: EDTA is 1:1:1.5; in step S12, the gel is kept at 600 °C for 4 hours for decarbonization, and then the obtained powder is placed in a muffle furnace and sintered at 800 °C for 5 hours.

9. The preparation method according to claim 6, characterized in that: In step S2, the binder is pinene alcohol containing 7.5-10 wt.% ethyl cellulose; the mass ratio of the precursor to the binder is 1:1.

5.

10. The preparation method according to claim 6, characterized in that: In step S3, the operating temperature is 800-900 °C, the reducing atmosphere is pure hydrogen, and the in-situ reduction time is 30-90 min.

Citation Information

Cited By

  • Symmetrical composite electrode and preparation method and application thereof

    CN119913555A

  • A symmetrical composite electrode, its preparation method and application

    CN119913555B

  • Perovskite cathode catalytic material for hydrogen production through solid oxide ammonia electrolysis and preparation of perovskite cathode catalytic material

    CN119956399A